Foliar morphological and micromorphological variation of dioscorea species in Terengganu, Malaysia - Abdullah, Nor Azahana; Abdullah Siam, Nordahlia; Mohd Yunus, Noor Syaheera; J., Hanissa; Noor Hashim, Noor Haslinda; H.S., Othman; M.S, Salleh (2023)
Dioscorea species are recognised for their production of tuberous roots and are referred to as "ubi" by the local population in Malaysia. The tubers of Dioscorea are commonly consumed by individuals residing in the East Coast region of Peninsular Malaysia as their primary food source. These tuberous roots are particularly abundant during the monsoon season, typically observed in local markets from October to December. Due to the availability and potential of this Dioscorea species, a study about the variation in morphological and micromorphological study of the leaves of three species of Dioscorea in Terengganu was conducted in order to identify the variation in their morphological and micromorphological characteristics. The selected species are D. esculenta (ubi itik), D. alata (ubi besar), and D. hispida (ubi gadong). The collection has been done in the Kuala Berang Terengganu area. The leaves morphological characteristics such as leaf colour, leaf type, leaf shape, leaf size, leaf margin and hairiness of adaxial and abaxial surface and shape of leaves and petiole were recorded. The morphological descriptors were suggested by the International Plant Genetic Resources Institute (IPGRI) / International Institute of Tropical Agriculture (IITA). The foliar anatomical studies of selected Dioscorea were followed by the standard tissue sectioning procedures and the observation was done by using light microscopy. The morphological study shows the variations in leaf shape, leaf base, and leaf size but they have the similarity in term of leaf margin shape and leaf attachment which is all species are petiolate. The micromorphological study shows the presence of non-glandular and uniseriate trichomes which is only obtained in the D. esculenta and D. hispida. Hence, this study contributes to the information on these species, especially for classification and identification of Dioscorea species.